Factor reumatoide IgM y antipéptido cíclico citrulinado como diagnostico presuntivo de artritis reumatoide en mujeres menopaúsicas en San Vicente de Caney-cantón Yantzaza - Herrera Lalangui, Lizbeth Salomé (2022)
Rheumatoid arthritis (RA) is an autoimmune disease that causes inflammation of the joints and surrounding tissues where genetic, environmental, ethnic, geographic and gender factors are involved, since women have a higher incidence of the disease. Two tests are performed in the laboratory to help determine AR; FR and Anti-CCP. The objective of this research work was to calculate the RF IgM and Anti-CCP values in 64 menopausal women from the community of San Vicente of Caney of the Yantzaza canton, complementing the classification criteria through a survey for a presumptive diagnosis of the disease. Through the statistical analysis SPSS edition 25, it was obtained that the mean IgM RF was 16.12 IU/ml with a frequency of 10.3% (n=8); and 4.48 IU/ml with a frequency of 1.3% (n=1) in Anti-CCP. Additionally, RF IgM and Anti-CPP levels were measured in 14 women of childbearing age from the community and similar ranges were obtained in both groups using the Mann Whiteny U test; menopausal women got 39.28 IU/ml and the control group presented 40.50 IU/ml in RF IgM; on the other hand, the value of Anti-CCP in menopausal women was 40.85 IU/ml and in the control group it was 33.32 IU/ml. Each patient was given a survey where it was found that 40 women had no signs of the disease, it is recommended to reassess 23 of them in a few months and only one of them complete the classification criteria with acute phase reactants. Concluding that the majority of women in this community do not have altered levels of RF IgM and Anti-CCP even though most of them had symptoms and the importance of the classification criteria, which helped identify whether or not the women suffered from RA